DEVELOPMENT OF TECHNICAL COMPETENCE OF EMPLOYEES THROUGH EDUCATION AND TRAINING (DIKLAT) IN MAKASSAR CITY - Yulianti J; Abdul Mahsyar; Burhanuddin; Fatmawati (INJOSEDU: International Journal of Social and Education, 2025)
This research aims to analyze the Pattern of ASN Education and Training Development at the Makassar City Regional Personnel Agency (BKD) and its implementation strategy in developing ASN competencies through technical training. This research approach uses descriptive qualitative. Data collection techniques through interviews and documentation. Seven research informants were selected purposively. The data analysis process was carried out with the help of NVivo 12 plus software. The results of this study indicate that: 1). The pattern of ASN technical training development carried out by the Makassar City Regional Staffing Agency is known that the training organized with the ADDIE model training approach has been running well as it should be guided by the curriculum issued by the State Administration Institute (LAN), but in its implementation it still refers to the trainings held so that the development has not been carried out properly, this is due to attachment to curriculum rules issued by LAN related to organizing training. 2). The strategy carried out by BKD Makassar City in implementing the training development pattern is to assess prospective training participants regarding their competencies before attending the training, making it easier to determine the material needed by employees in developing their competencies, especially those related to technical matters.